Do enterprise risk management practices and ESG performance influence firm value of banks? Evidence from ASEAN countries - Denia, Adiva Putri; Sukmadilaga, Citra; Ghani, Erlane K (Asian Journal of Economic Modelling, 2024)
This study investigates the impact of enterprise risk management (ERM) practices and environmental, social, and governance (ESG) performance on firm value both individually and collectively, within the context of five ASEAN nations. This study used a dataset consisting of annual reports over a two-year timeframe (2021–2022) from a total of 29 banks that are publicly listed on the stock exchanges in Indonesia, Malaysia, Singapore, Thailand, and the Philippines. The results of this study indicate that ESG performance has a statistically significant positive impact on firm value. However, the effect of ERM practices on firm value is shown to be positive but lacks statistical significance. The findings also indicate that the combined influence of ERM procedures and ESG performance has a positive effect on company value, while the impact is statistically insignificant. According to the study’s findings, the impact of the variables under investigation on firm value may account for a sizable portion of them, or 71.8%. The results of this study suggest that companies should adopt a consistent enterprise risk management (ERM) approach to enhance the accessibility of ERM-related information. This will ensure that investors are not only reliant on quantitative outcomes from a company, which may aid in their investment decision-making process. This study provides new insights for investors on the influence of ERM practices and ESG performance on the firm value of banks in developing countries, especially in ASEAN countries.